The role of cystectomy in elderly patients – a multicentre analysis. (2nd September 2015) - Izquierdo, Laura; Peri, Lluis; Leon, Priscila; Ramírez‐Backhaus, Miguel; Manning, Thomas; Alcaraz, Antonio; Roupret, Morgan; Solsona, Eduardo; Rubio, Jose; Sengupta, Shomik; Chan, Yee; Liodakis, Peter; et al.
Abstract : Introduction: Life expectancy in developed countries is continuously increasing. Hence elderly patients are becoming more common in our clinical practice. Currently, one of the greatest challenges of medicine is balancing the life expectancy of elderly patients against aggressive treatments that carry significant risks. Objective: To outline the complications and survival in surgical patients 80 years and over undergoing radical cystectomy for bladder cancer. Patients and Methods: A review of a radical cystectomy in elderly recorded in four different institutional prospective databases during the period between 1991 and 2014. Clinical and pathologic features, complications and survival were evaluated. Results: A total of 111 patients were available. Median (range) age 82.2 (80–89) years. Seventeen women and 94 men. Regarding the ASA score, 6 patients were ASA I, 47 patients were ASA II, 49 patients ASA III and 9 ASA IV. Prior to surgery, 48 patients had hydronephrosis. The median (range) creatinine series was 1.1 (0.71–11.1) ng/dL. In 88 cases an ileal conduit was performed, 17 a cutaneous ureterostomy diversion, 5 neobladders and 1 ureterosigmoidostomy case. The median (range) operative time was 230 (120–420) min and a total of 97 patients required blood transfusion. The median (range) hospital stay was 14 (7–126) days. The early and late complication rates were 50.4% and 32%, respectively. A total of 14 patients (12.6%) required surgical reintervention. Eight patients (7.2%) died in the immediate postoperative period. The readmission rate of the series was 27.2%. The mean follow‐up of the series was 18 (0.27–134.73) months. During this period 66 patients died, 52 of them due to the tumor. Twelve month tumour progression free survival was 83.9% for ≤pT1, 70.2% for pT2 and 36% for ≥pT3, respectively. Twelve month cancer specific survival was 85.6% for ≤pT1, 75.1% for pT2 and 42.5% for ≥pT3, respectively. Conclusion: Radical cystectomy in elderly population is an aggressive surgical treatment with a significant complication rate, hospital readmission and perioperative mortality rate. Careful selection of patients is essential in order to minimize the complications of this surgery and balance benefits against risks in the elderly population. Tumour progression and cancer specific survival are poor for patients with ≥pT3 disease. Alternatives such as tri‐modality therapy need to be considered within a multi‐disciplinary approach. More data is required to determine which sub‐groups of elderly patients would benefit from a complication, survival and quality of life perspective.